"What Is the Matter With Me?" or a "Badge of Honor": Nurses' Constructions of Resilience During Covid-19. (April 2022) - Conolly, Anna; Abrams, Ruth; Rowland, Emma; Harris, Ruth; Couper, Keith; Kelly, Daniel; Kent, Bridie; Maben, Jill
It has long been known that nursing work is challenging and has the potential for negative impacts. During the COVID-19 pandemic most nurses' working landscapes altered dramatically and many faced unprecedented challenges. Resilience is a contested term that has been used with increasing prevalence in healthcare with health professionals encouraging a "tool-box" of stress management techniques and resilience-building skills. Drawing on narrative interview data ( n = 27) from the Impact of Covid on Nurses (ICON) qualitative study we examine how nurses conceptualized resilience during COVID-19 and the impacts this had on their mental wellbeing. We argue here that it is paramount that nurses are not blamed for experiencing workplace stress when perceived not to be resilient "enough, " particularly when expressing what may be deemed to be normal and appropriate reactions given the extreme circumstances and context of the COVID-19 pandemic.